Anatomical variants of profunda femoris artery : Among cadavers from South India - K Vishal; K V Vinay; K Shishir; A Y Raghavendra (Wolters Kluwer Medknow Publications, 2014)
Background: The profunda femoris artery (PFA) is a branch of femoral artery which plays an important role in the arterial supply of the thigh. An extensive knowledge of the branching pattern and relations are necessary for clinicians to prevent any iatrogenic damage to these blood vessels and the surrounding structures in vascular reconstructive surgeries. Objective: To study the direction of origin of PFA from femoral artery and measure DIP- the distance between the origin of PFA from femoral artery to midpoint of inguinal ligament. Materials and Methods: Forty six femoral triangles (23 on right & 23 on left side) were dissected and studied in embalmed cadavers available in dissection hall of K. S. Hegde Medical Academy, Mangalore, India over a period of two years from July 2011 to July 2013. These cadavers were of South Indian origin. The direction of origin of PFA from femoral artery was noted. The DIP was measured using Vernier caliper. Results: The direction of origin of the PFA in majority of the cases was found to be from the posterolateral side (65.22%) of femoral artery. The DIP varies from 25 to 50 mm on the right and 24 to 60 mm on the left side. In 50 % of the cases, the DIP was in the range of 41 to 50 mm on both the sides. Conclusion: The anatomical data obtained here is of importance for surgeons and radiologists for procedures centred on the PFA and in vascular reconstructive surgeries involving the groin.